Juvenile Spring Eruption: A Variant of Perniosis?. (September 2015) - Nabatian, Adam S.; Rosman, Ilana S.; Sturza, Jeffrey; Jacobson, Mark
Abstract : Abstract: Juvenile spring eruption (JSE) is a unique condition that typically affects the helices of the ears of boys and young men. The classical clinical picture of JSE includes the abrupt onset of lesions after spending time outdoors in the early spring. Because of the papulovesicular nature of the rash and the history of sun exposure, JSE is considered a variant of polymorphous light eruption. In addition to the term "juvenile spring eruption, " this entity has also been described under other less common terms such as "perniosis juvenilis vernalis aurium" or "spring perniosis, " which emphasizes the onset in the spring and the possible pathogenic role of cold weather. We present a case of likely JSE with histopathologic features more consistent with perniosis than polymorphous light eruption and present a review the literature.